Clustering and Portfolio Optimization on LQ45 Stocks with Fuzzy C-Means and Single Index Model - Gunawan, Risky; Owen, Geraldo (Jurnal Matematika, Statistika dan Komputasi, 2025)
Spreading money or capital across several assets through portfolio formation is more recommended when investing in stocks. The selection of the optimal portfolio can use the Fuzzy C-Means and Single Index Model methods. This research used stock data on the LQ45 Index from January 27, 2020, to November 27, 2024, with the results of 3 portfolios formed. Portfolio 1 has members ADRO, ANTM, and PTBA with an expected return value of 0.001123 and a risk of 0.000670 with a sharpe index performance of 1.393. Portfolio 2 has members BBNI, BMRI, and INCO with an expected return value of 0.000456 and a risk of 0.000524 which has a sharpe index of 0.509. Portfolio 3 with BBCA and INKP has an expected return of 0.000343 and a risk of 0.000453 with a performance of 0.338. For investors who are very risk tolerant, it is recommended to invest in portfolio 1, and for investors who are slightly risk tolerant, portfolio 2 will be suitable, and for investor who are intolerant of risk, portfolio 3 is more suitable. Based on the results obtained in this study, it can be concluded that portfolio building through clustering from Fuzzy C-Means and continued by portfolio weighting based on the Single Index Model produces an optimal portfolio with a fairly high sharpe index performance.